Label-free Live and Dead Cell Separation Method Using a High-Efficiency Optically-Induced Dielectrophoretic (ODEP) Force-based Microfluidic Platform - Huang, Song-Bin; Liu, Shing-Lun; Li, Jian-Ting; Wu, Min-Hsien (International journal of automation and smart technology, 2025)
This study reports an optically-induced dielectrophoretic (ODEP) force-based microfluidic platform for live and dead cell separation and collection. ODEP forces are used to separate the live and dead cells due to their opposite responses to an ODEP force. Combining the flow control in a microfluidic system, the live and dead cells can be separated and subsequently collected in an efficient and effective manner. The operating conditions of the ODEP force for manipulating the live and dead chondrocytes is characterized, and separation performance is experimentally evaluated. Results revealed that an applied voltage of 8 V resulted in a maximum difference of manipulation force for the live (49.4 pN) and dead (-20.1 pN) cells. Results of further separation experiments showed that the recovery rate and purity of the isolated live cells was as high as 78.3±6.8 % and 96.4 ±2.2 %, respectively. Overall, the proposed method is found to be particularly valuable for biological research which requires the isolation of highly pure live or dead cells.